2007
DOI: 10.5713/ajas.2007.1729
|View full text |Cite
|
Sign up to set email alerts
|

Can Exogenous Betaine Be an Effective Osmolyte in Broiler Chicks under Water Salinity Stress?

Abstract: A CRD experiment was conducted to evaluate the effects of different exogenous betaine levels (0.000, 0.075, 0.150 and 0.225 percent) on 576 one-day-old male broiler chicks (Ross) under water salinity stress. Different levels of water salinity were made by adding 3 levels of NaCl (0, 1,000 and 2,000 mg/L) to drinking water. Feed and water were available ad libitum. Betaine increased body weight, improved feed conversion ratio, and decreased packed cell volume (p<0.05). Water salinity promoted body weight over t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
4
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 28 publications
2
22
4
2
Order By: Relevance
“…Other studies also showed that supplementation of choline or BET increased ADG of birds fed diets marginally deficient in Met [19][20] . Furthermore, betaine is an osmolyte that could improve intestinal structure and function to increase growth performance [21,22] . It appears, thus, that BET and Met in marginally Metdeficient diets could lead to an equivalent growth response in broilers and that BET could spare a small portion of the Met.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies also showed that supplementation of choline or BET increased ADG of birds fed diets marginally deficient in Met [19][20] . Furthermore, betaine is an osmolyte that could improve intestinal structure and function to increase growth performance [21,22] . It appears, thus, that BET and Met in marginally Metdeficient diets could lead to an equivalent growth response in broilers and that BET could spare a small portion of the Met.…”
Section: Discussionmentioning
confidence: 99%
“…In a research, Honarbakhsh et al (2007) reported the increased water consumption and litter moisture of chickens with increasing of water salinity. They also found the decreasing of packed cell volume by betaine supplementation.…”
Section: Introductionmentioning
confidence: 99%
“…However, saline water decreased the forequarter weight and the weights of non-edible and edible organs, but the hot carcass weight and dressing percentage were not affected by water salinity. Moreover, Honarbakhsh et al (2007) showed that saline water (1,000 and 2,000 mg TDS/l ) improved the breast yield (P<0.01) of broiler chicks, but slightly decreased the abdominal fat and sartorial percentages compared with fresh water group On the contrary, many studies reported that saline water did not influence carcass traits. Such as, Walker et al (1971) found that the carcass weight was not affected in Merino wethers consuming saline or tap water.…”
Section: Effect Of Saline Water On Carcass Characteristicsmentioning
confidence: 96%